Plasma calprotectin as an indicator of need of transfer to intensive care in patients with suspected sepsis at the emergency department - Åsa Parke; Christian Unge; David Yu; Jonas Sundén-Cullberg; Kristoffer Strålin (BMC Emergency Medicine, 2023)
Abstract Background Deciding whether to transfer patients with sepsis from the emergency department (ED) to intensive care units (ICUs) is challenging. We hypothesised that the new biomarker plasma calprotectin (p-calprotectin) could be used to aid the selection of patients for intensive care transfer, since it has been shown to be a promising tool for the determination of sepsis severity in critical care. Methods This prospective study was performed on consecutive sepsis alert patients in the ED of Karolinska University Hospital Huddinge. The sepsis alert mandates clinical assessment and decisions regarding treatment, disposition, and level of care by physicians from the ED, the Department of Infectious Diseases, and the ICU. Blood sample analysis for C-reactive protein, procalcitonin, neutrophils, and lymphocytes was routinely performed. P-calprotectin was analysed from frozen plasma samples, using a specific turbidimetric assay. Results Three-hundred fifty-one patients who triggered the sepsis alert were available for the study. Among 319 patients who were considered to have an infection, 66 patients (26%) were immediately transferred to the ICU or high-dependency unit (HDU), and 253 patients (74%) were transferred to ordinary wards. Median p-calprotectin was 2.2 mg/L (IQR 1.2–3.9 mg/L) for all patients with infection, it was 3.3 (IQR 1.6–5.2) for those transferred to ICU/HDU and 2.1 (IQR 1.1–3.5) for those transferred to ward units (p = 0.0001). Receiver operating characteristic curve analysis for transfer to the ICU/HDU showed superiority for p-calprotectin compared with procalcitonin and neutrophil–lymphocyte ratio, regarding both all sepsis alert cases and the patients with infection (p < 0.001 for all comparisons). The best p-calprotectin cut-off, 4.0 mg/L, showed a sensitivity of 42.5% and specificity of 83% for transfer to the ICU/HDU among patients with infection. Conclusions In sepsis alert patients, p-calprotectin was significantly elevated in patients who were subject to immediate ICU/HDU transfer after assessment by a multidisciplinary team. P-calprotectin was superior to traditional biomarkers in predicting the need for transfer to the ICU/HDU.